Proof of Concept: The Use of Whole-Slide Images (WSI) for Peer Review of Tissues on Routine Regulatory Toxicology Studies. (June 2021) - Bradley, Alys E.; Cary, Maurice G.; Isobe, Kaori; Naylor, Stuart; Drew, Stephen
This Proof of Concept (POC) study was to assess whether assessment of whole slide images (WSI) of the 2 target tissues for a contemporaneous peer review can elicit concordant results to the findings generated by the Study Pathologist from the glass slides. Well-focused WSI of liver and spleen from 4 groups of mice, that had previously been diagnosed to be the target tissues by an experienced veterinary toxicologic pathologist examining glass slides, were independently reviewed by 3 veterinary pathologists with varying experience in assessment of WSIs. Diagnostic discrepancies were then reviewed by an experienced adjudicating pathologist. Assessment of microscopic findings using WSI showed concordance with the glass slides, with only slight discrepancy in severity grades noted. None of the lesions recorded by the Study pathologist were "missed" and no lesions were added by the pathologists evaluating WSIs, thus demonstrating equivalence of the WSI to glass slides for this study.